PENGARUH LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN INDEKS LQ45 DI BEI - Inge Shintia; Yusbardini Yusbardini (PROSIDING SERINA, 2021)
Financial performance is important in maintaining the sustainability of the company. Good financial performance shows the company is able to compete in competitive advantage. The purpose of this study was to determine the effect of leverage, liquidity and firm size on financial performance. The population of this study is the LQ45 index on the IDX with the research year 2015 to 2019. The sampling technique is based on purposive sampling. The total research sample was 45 observations. The data used is secondary data, using multiple regression analysis. The data analysis program used is eviews9. The results showed that partially leverage showed a positive and significant effect on financial performance, liquidity had no effect on financial performance, and firm size showed a significant negative effect on financial performance.